Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

let Tr=r th term of an ap. m.Tm=n.Tn,show that Tm+n=0

let Tr=r th term of an ap. m.Tm=n.Tn,show that Tm+n=0

Grade:11

1 Answers

Vikas TU
14149 Points
3 years ago
r th term of an ap= Tr 
m th term of an ap= Tm 
n th term of an ap= Tn 
As indicated by question m.Tm=n.Tn 
m(a + (m-1)d = n(a + (n-1)d) 
Where an is the principal term and d is the normal distinction 
mama – na + (m^2 – m)d - (n^2 –n)d 
a(m-n) + d(m-n){m+n-1} = 0 
a + (m+n-1)d = 0 
Tm+n=0 
Thus Proved 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free